Extracorporeal Shockwave Therapy Accelerates the Healing of a Meniscal Tear in the Avascular Region in a Rat Model. Issue 12 (October 2019) - Hashimoto, Shogo; Ichinose, Tsuyoshi; Ohsawa, Takashi; Koibuchi, Noriyuki; Chikuda, Hirotaka
Background: The treatment of meniscal tears in the avascular region remains a clinical challenge. Extracorporeal shockwave therapy (ESWT) is a minimally invasive, safe, and effective therapy for various orthopaedic disorders. However, the therapeutic effect of ESWT on meniscal tears has not been reported. Purpose: To evaluate the therapeutic effect of ESWT in the treatment of meniscal tears. Study Design: Controlled laboratory study. Methods: Twelve-week-old male Wistar rats were divided into 3 groups (normal, ESWT–, and ESWT+). The authors made a full-thickness 2-mm longitudinal tear in the avascular region of the anterior horn in the latter 2 groups. At 1 week after surgery, the ESWT+ group received 800 impulses of shockwave at 0.22-mJ/mm 2 energy flux density in a single session. The authors performed a histological examination to evaluate meniscal healing (n = 10 for each group) and immunohistochemistry to analyze the expression of bromodeoxyuridine (BrdU; n = 5 for each group) and CCN family member 2/connective tissue growth factor (CCN2/CTGF; n = 5 for each group) at 2, 4, and 8 weeks after ESWT. The mRNA levels of CCN2, SOX 9, VEGF-a, aggrecan, Col1a2, and Col2a1 at the site of the meniscal tear at 4 weeks after ESWT were quantitatively evaluated by a real-time polymerase chain reaction (n = 5 for each group). Results: The meniscus healing scores in the ESWT+ group were significantly higher than those in the ESWT– group at 4 weeks and 8 weeks. The ratio of BrdU-positive cells was the highest in the ESWT+ group at all observation periods. The ratio of CCN2-positive cells was highest in the ESWT+ group at 4 and 8 weeks. In the ESWT+ group, real-time polymerase chain reaction revealed that the levels of CCN2, SOX9, aggrecan, and Col2a1 were upregulated (All significant data were P < .05). Conclusion: ESWT promoted the healing of meniscal tears in the avascular area. ESWT stimulated proliferation of meniscal cells and the upregulation of cartilage-repairing factors such as CCN2, with the upregulation of cartilage-specific extracellular matrix expression. Clinical Relevance: ESWT may be an effective therapeutic option that promotes meniscal healing in the avascular region.